A New Approach to Spyware Classification Using a 1D-Gaussian Filter on Network Packets - Kilic, Irfan; Yaman, Orhan (Institute of Electrical and Electronics Engineers Inc., 2024)
The Windows operating system is the most widely used system by end users. Therefore, spyware is popular in this system. This study used a dimension (1D)-Gaussian filter to detect such infiltrations very quickly. For this purpose, a 4-class dataset obtained in a laboratory environment was used. A new approach classifies Gaussian-filtered network packets using Decision Trees (DT). Recursive Feature Elimination (RFE) was used, which gave good results for comparison. The results obtained show that the study achieved its objective. © 2024 IEEE.
8th International Artificial Intelligence and Data Processing Symposium, IDAP 2024 -- 21 September 2024 through 22 September 2024 -- Malatya -- 203423
Keywords: classification; decision trees; Gaussian filter; recursive feature elimination; spyware